Can India grow without Bharat? - "Acharya, Shankar" (New Delhi, 2007)
An insightful analysis that pro-vides forthright and provocative responses to key development issues in India, this work tackles issues like economic growth, foreign affairs, employment challenges, and tax policies.
Keywords: Economic development-India